Treatment options for deciduous molar hypomineralization: A report of three cases - Quintero, Yasmy [UNESP]; Restrepo, Manuel; Saldarriaga, Jenny Angélica [UNESP]; Saldarriaga, Alexandra [UNESP]; Santos-Pinto, Lourdes [UNESP] (My University, 2019)
Deciduous molar hypomineralization (DMH) is an enamel defect of systemic and multifactorial origin that affects the second deciduous molar. Currently, its treatment is based on guidelines for Molar Incisor Hypomineralization (MIH), a disturbance that affects permanent molars and may or may not be associated with permanent incisors. To date, there are no guidelines for DMH. Therefore, three different therapeutic approaches are presented to treat DMH, emphasizing the relevance of early diagnosis, differential diagnosis and treatment options, and tailored to take into account each patient’s and parents’ specific needs, as well as the involved tooth, severity of DMH, patients’ symptoms and behaviour.